HARMONISASI PRINSIP SYARIAH DAN EQUAL EMPLOYMENT OPPORTUNITY DALAM PENGELOLAAN KEBERAGAMAN - Rachma Febriyanti; Muhammad Rafli; Abdul Wahab; Alim Syariati (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the harmonization of Islamic principles and Equal Employment Opportunity (EEO) in workforce diversity management. The study employs a qualitative approach using a library research method. Data were collected from scholarly journal articles, International Labour Organization (ILO) documents, labor regulations, and relevant literature discussing equal employment opportunity, diversity management, and Islamic principles. The data were analyzed using content analysis through the processes of identifying, categorizing, and synthesizing relevant concepts. The findings indicate that Islamic principles are strongly aligned with the objectives of EEO and diversity management. The values of justice (al-'adl), human equality (al-musawah), trustworthiness (amanah), and the protection of human dignity (hifz al-'irdh) provide ethical and normative foundations for promoting equal employment opportunities and fostering inclusive workplaces. The study also finds that implementation challenges remain in the form of age discrimination, limited employment access for persons with disabilities, gender inequality, social stereotypes, and organizational cultures that do not fully support inclusiveness. Therefore, the harmonization of Islamic principles and EEO can serve as an approach to strengthening human resource management practices in creating fair, inclusive, and sustainable workplaces.